2019
DOI: 10.1111/caje.12379
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in university enrolment: Do parents play a role beyond investing in skills?

Abstract: Young men are far less likely than women to attend university across most OECD countries. I use data from the Youth in Transition Survey (YITS) to investigate this issue in the Canadian context, focusing on how parents might influence this gender gap. In particular, my goal is to isolate the incremental effect of parents’ valuations of education during the teenage years, holding constant the stock of skills acquired up to that point. To estimate this effect, I use a factor model based on a framework developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(167 reference statements)
0
2
0
1
Order By: Relevance
“…Second, another possibility is to promote more vigorously summer learning programs and related educational enrichment opportunities, initiatives that research has shown are beneficial for children from less advantaged backgrounds (Davies & Aurini, 2013). Third, leveraging the influence of parents, as promoted by the Millennium Scholarship program's “Future to Discover,” is another strategy given the importance parent's valuation of education has on their offspring (Foley, 2019). Finally, another option, although more controversial, would be to increase the mandatory school leaving age to 18 thereby providing a greater likelihood that the high school dropout rate will decline even further (Oreopoulos, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Second, another possibility is to promote more vigorously summer learning programs and related educational enrichment opportunities, initiatives that research has shown are beneficial for children from less advantaged backgrounds (Davies & Aurini, 2013). Third, leveraging the influence of parents, as promoted by the Millennium Scholarship program's “Future to Discover,” is another strategy given the importance parent's valuation of education has on their offspring (Foley, 2019). Finally, another option, although more controversial, would be to increase the mandatory school leaving age to 18 thereby providing a greater likelihood that the high school dropout rate will decline even further (Oreopoulos, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Le défi social de réduire les disparités en littéracie reste impérieux, en plus du décrochage scolaire des garçons au Québec. Si des données observationnelles indiquent que dans certaines écoles les filles, les Asiatiques ou les enfants des professeurs d'université font très bien, elles ne permettent pas de montrer si ce groupe obtient de meilleurs résultats parce qu'il fréquente de meilleures écoles ou fait mieux à cause de facteurs sociaux ou biologiques sans lien avec l'école fréquentée (Foley et al, 2014;Foley, 2019). Modifier les comportements éducatifs parentaux est une tâche difficile.…”
Section: Discussionunclassified
“…The sample is representative for the general population of working adults in Poland in terms of age. However, the gender gap [overrepresentation of women, typical for university education (Baker, 2016 ; Foley, 2019 )] and the level of education (at least secondary) limit the generalization of results.…”
Section: Methodsmentioning
confidence: 99%